2019
DOI: 10.1371/journal.pone.0208505
|View full text |Cite
|
Sign up to set email alerts
|

ESBL colonization and acquisition in a hospital population: The molecular epidemiology and transmission of resistance genes

Abstract: A prospective cohort study (German Clinical Trial Registry, No. 00005273) was performed to determine pre-admission colonization rates, hospital acquisition risk factors, subsequent infection rates and colonization persistence including the respective molecular epidemiology and transmission rates of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae (EPE). A total of 342 EPEs were isolated from rectal swabs of 1,334 patients on admission, at discharge and 6 months after hospitalization. Inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 30 publications
4
40
1
Order By: Relevance
“…Őstholm-Balkhed et al, 2013 48 Prasad et al, 2016 49 Goodman et al, 2019 36 Hagel et al, 2019 42 Kuenzli et al, 2014 44 Lee et al, 2018 46 1 Subtotal (95% CI) Heterogeneity: τ 2 = 0.04; χ 2 = 8.68, df = 6 (P = .19); I 2 = 31% Test for overall effect: z = 4.74 (P<.001)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Őstholm-Balkhed et al, 2013 48 Prasad et al, 2016 49 Goodman et al, 2019 36 Hagel et al, 2019 42 Kuenzli et al, 2014 44 Lee et al, 2018 46 1 Subtotal (95% CI) Heterogeneity: τ 2 = 0.04; χ 2 = 8.68, df = 6 (P = .19); I 2 = 31% Test for overall effect: z = 4.74 (P<.001)…”
Section: Discussionmentioning
confidence: 99%
“…We divided the 15 hospital-based studies into 2 groups: 4 studies 9,36,37,43 evaluated colonization at admission (sc reening w ithin 48 hours of admission), and 11 studies 15,[38][39][40][41][42]46,47,50,52,53 I 2 = 33%); 4 community-based studies 10,51,54,57 showed similar results but with a slightly smaller association (OR = 1.41; 95% CI, 1.07-1.87; I 2 = 21%). However, meta-analysis of 4 travelbased studies 8,44,48,56 yielded an OR with a very broad CI (OR = 1.11; 95% CI, 0.82-1.50; I 2 = 0%) (eFigure 4 in the Supplement).…”
Section: By Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that resistance traits can be transferred from individual bacteria to other individual bacteria, and in rare cases even between species (Bosch et al 2017;Lindblom et al 2019). Consequently, to the extent that individuals develop symptoms by resistant bacteria due to an MDRGN colonisation, these may not be the bacteria targeted by screening, but rather from other bacteria in their gut adopting the same plasmid (Hagel et al 2019). A potentially effective program would therefore have to focus not on particular drug resistant bacteria types, but also on the resistant mechanism for early identification of polyclonal outbreaks that may involve interspecies plasmid migration (Müller et al 2016).…”
Section: Epidemiological Comparison Mrsa Vs Mdrgnmentioning
confidence: 99%
“…Most bacterial species are able to integrate different determinants of resistance into their genome. Thus, the dissemination of resistance genes between bacteria has led to the appearance of bacteria resistant to several antibiotics in particular the strains of Staphylococcus aureus resistant to methicillin (MRSA), the enterobacteria producing betaextended spectrum lactamases (ESBL) and vancomycin resistant enterococci (VRE) [8,9,10]. Among bacteria resistant to antibiotics, enterobacteria producing broad spectrum β-lactamase (ESBL) represent a major global threat in hospitals [8].…”
Section: Introductionmentioning
confidence: 99%